Comparative Design of Structures Concepts and Methodologies - Lin, Shaopei; Huang, Zhen (Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book presents comparative design as an approach to the conceptual design of structures. Primarily focusing on reasonable structural performance, sustainable development and architectural aesthetics, it features detailed studies of structural performance through the composition and de-composition of these elements for a variety of structures, such as high-rise buildings, long-span crossings and spatial structures. The latter part of the book addresses the theoretical basis and practical implementation of knowledge engineering in structural design, and a case-based fuzzy reasoning method is introduced to illustrate the concept and method of intelligent design. The book is intended for civil engineers, structural designers and architects, as well as senior undergraduate and graduate students in civil engineering and architecture. Shaopei Lin and Zhen Huang are both Professors at the Department of Civil Engineering, Shanghai Jiao Tong University, China.